(untitled) - Vorpérian, Vatché (Cambridge, 2002)
The only current method of circuit analysis known to most engineers and students is nodal, or loop, analysis. Although it works well for obtaining numerical solutions, the method is almost useless for obtaining analytical solutions in all but the simplest cases. In this unique book, Vorpérian describes remarkable alternative techniques to solve complicated linear circuits in symbolic form and obtain meaningful analytical answers for any transfer function or impedance. Although not intended to replace traditional computer-based methods, these techniques provide engineers with a powerful set of tools for tackling circuit design problems. They also enhance understanding of circuit operation, making this an ideal course book, and numerous problems and worked examples are included. Originally developed by Professor David Middlebrook and others at the California Institute of Technology, the techniques are now widely taught at institutions and companies worldwide.
Keywords: Electronic circuits,Electric circuits,Electric circuit analysis,Mạch điện tử,Mạch điện,Phân tích mạch điện